Malaysia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper describes economic developments in Malaysia in 1998. Most major sectors recorded lower output in 1998, with the manufacturing and construction sectors among the hardest hit. Manufacturing output contracted by 10.2 percent in 1998, following strong, robust growth averaging 13.5 percent in 1994-97. Falling domestic demand and, to a lesser extent, weaker overseas orders were the major factors behind the decline. The decline, which gathered momentum over the course of the year, was broad-based across industries, and was more pronounced in industries producing construction-related materials and transport equipment.